El ABP para el aprendizaje de Biodiversidad del Ecuador flora, fauna y especies en peligro de extinción con los estudiantes de sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Ulloa Montaño, Iván Patricio (2024)
The research examined the shortcomings of conventional teaching methods, which often focus on memorization instead of encouraging reasoning. Problem-Based Learning promotes the development of students' critical and analytical thinking by confronting problems that must be solved with viable solutions. This research aimed to propose PBL for Learning about Ecuador's Biodiversity, flora, fauna, and endangered species with sixth-semester students of the Experimental Sciences Pedagogy Program in Chemistry and Biology, 2024-1S. The methodology used had a non-experimental bibliographic and field-type design with a descriptive research level. For data collection, the survey was applied as a technique, and the questionnaire was used as an instrument, and the study population consisted of 20 students. As a result, the digital guide "Whisper of Gaia's Oracle" was elaborated, contributing to the acquisition of theoretical knowledge and the analysis of real problems, promoting awareness about the care of biodiversity. In conclusion, the implementation of this methodology and the digital guide positively impacted the educational process.